2009
DOI: 10.1105/tpc.108.063768
|View full text |Cite
|
Sign up to set email alerts
|

ARABIDOPSIS DEHISCENCE ZONE POLYGALACTURONASE1 (ADPG1), ADPG2, and QUARTET2 Are Polygalacturonases Required for Cell Separation during Reproductive Development inArabidopsis 

Abstract: Cell separation is thought to involve degradation of pectin by several hydrolytic enzymes, particularly polygalacturonase (PG). Here, we characterize an activation tagging line with reduced growth and male sterility caused by increased expression of a PG encoded by QUARTET2 (QRT2). QRT2 is essential for pollen grain separation and is part of a small family of three closely related endo-PGs in the Arabidopsis thaliana proteome, including ARABIDOPSIS DEHISCENCE ZONE POLYGALACTURONASE1 (ADPG1) and ADPG2. Function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
415
2
8

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 369 publications
(433 citation statements)
references
References 85 publications
(124 reference statements)
8
415
2
8
Order By: Relevance
“…In the case of flagellin and EF-Tu, conserved short peptide motifs are sufficient to trigger similar responses as the proteins that they are derived from Brunner et al, 2002;Kunze et al, 2004). Amino acid sequence alignment of several fungal PGs and three Arabidopsis PGs (Ogawa et al, 2009) showed that an 11-amino acid stretch, just downstream of the catalytic site, is highly conserved among fungal PGs ( Supplemental Fig. S7); the homologous region in Arabidopsis PGs contains a Gly-to-Pro substitution.…”
Section: Rbpg1 Recognizes Multiple Active and Inactive Pgs But Not Amentioning
confidence: 99%
“…In the case of flagellin and EF-Tu, conserved short peptide motifs are sufficient to trigger similar responses as the proteins that they are derived from Brunner et al, 2002;Kunze et al, 2004). Amino acid sequence alignment of several fungal PGs and three Arabidopsis PGs (Ogawa et al, 2009) showed that an 11-amino acid stretch, just downstream of the catalytic site, is highly conserved among fungal PGs ( Supplemental Fig. S7); the homologous region in Arabidopsis PGs contains a Gly-to-Pro substitution.…”
Section: Rbpg1 Recognizes Multiple Active and Inactive Pgs But Not Amentioning
confidence: 99%
“…An Arabidopsis seed AZ is composed of a few thin layers of small cells that differentiate after fertilization. Investigations of seed AZdeficient mutants revealed that differentiation of the AZs requires the MADS-box TF gene SEEDSTICK (STK) and the bHLH family TF gene HECATE3 (HEC3) (Ogawa et al 2009;Pinyopich et al 2003). Seeds of the plants with loss-of-function mutations in STK and HEC3 lack AZs and thus remain attached to the pods even when the seeds are fully mature.…”
Section: Seed Abscissionmentioning
confidence: 99%
“…However, a recent Arabidopsis study provided new evidence that JA and ABA act in the regulation of the floral organ abscission (Ogawa et al 2009). That study found that the JA-deficient allene oxide synthase (aos) mutants and the ethylene insensitive ein2 mutants showed delayed floral organ abscission; moreover, the delay increased additively in the ein2 aos double mutants.…”
Section: Hormonal Regulation Of Organ Abscissionmentioning
confidence: 99%
“…When the dehiscing force exceeds the binding strength of the pod walls, the pod dehisces and seeds are dispersed. In Arabidopsis thaliana, several shattering-resistant mutants have been isolated, and the associated genes and mechanisms have been identified (5)(6)(7)(8)(9)(10). In shattering-resistant (SR) mutants, the formation of abscission layers between valves and the replum is inhibited by two factors: defects in transcriptional factors regulating fruit patterning (6-9), or secondary cell wall formation (10), and the absence of polygalacturonase that degrades pectin, an adhesive polysaccharide binding the walls of adjacent cells (5).…”
mentioning
confidence: 99%